2018
DOI: 10.1111/raq.12307
|View full text |Cite
|
Sign up to set email alerts
|

Insight into aquaculture's potential of marine annelid worms and ecological concerns: a review

Abstract: Polychaetes are marine annelid worms that can contribute to aquaculture diversification. Its culture has been viable, and commercially attempted, but intensive production has progressed only in few countries around the world. In the countries with no production, marine polychaetes are imported or harvested. A strong and sustained research investment provided to a better understanding of the nutritional requirements and reproduction of some species. Recent studies showed new technical improvements, which can le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 72 publications
0
30
0
1
Order By: Relevance
“…According to reported values, approximately 121.000 tons of polychaetes (with an estimated value of USD 8.39 billion) were harvested globally in 2015, with these figures being comparable to some of the most important world fisheries (Watson et al, 2016). It has already been acknowledged that the collection of polychaetes from the wild is likely insufficient to satisfy global market demands and that this practice drives a multitude of negative environmental impacts (Fidalgo e Costa et al, 2006;Pombo et al, 2018;Xenarios et al, 2018). The polychaete Hediste diversicolor O.F.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to reported values, approximately 121.000 tons of polychaetes (with an estimated value of USD 8.39 billion) were harvested globally in 2015, with these figures being comparable to some of the most important world fisheries (Watson et al, 2016). It has already been acknowledged that the collection of polychaetes from the wild is likely insufficient to satisfy global market demands and that this practice drives a multitude of negative environmental impacts (Fidalgo e Costa et al, 2006;Pombo et al, 2018;Xenarios et al, 2018). The polychaete Hediste diversicolor O.F.…”
Section: Introductionmentioning
confidence: 99%
“…The polychaete Hediste diversicolor O.F. Müller, 1776, popularly known as ragworm, is a highly valued bait species for sports fishing (Fidalgo e Costa et al, 2006;Carvalho et al, 2013;Sá et al, 2017;Pombo et al, 2018). It also plays a key dietary role on the nutrition and production of some fish and crustacean species (e.g., soles, shrimps and crabs), being often used to trigger gonad maturation and spawning (Lytle et al, 1990;Dinis, 1992;Luis and Ponte, 1993;Dinis et al, 1999;Meunpol et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The role of the polychaete may be direct through the consumption of faecal pellets at the sediment surface or indirect through the stimulation of bacterial processes in deeper sediment layers. Further worm species have been identified that could help mitigate aquaculture wastes while producing additional farmed marine biomass in integrated multitrophic aquaculture (IMTA) (Pombo et al, 2018).…”
Section: Predicting the Impacts Of Bivalve Aquaculture On The Benthicmentioning
confidence: 99%
“…With the increasing demand for polychaetes both from recreational fishing industry and aquaculture, the culture of polychaetes has become a sustainable alternative (Pombo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%